Knowledge Transfer Challenges: A Practical Study of Yemen Public Telecommunication Corporation - Al-Taweel, Sadik; Ali, Ghassan Ahmed; Alhazbi, Saleh; Yousef, Walid; Al-Fuhaidi, Belal; Albater, Thamer; Hezzam, Essa; Ghallab, Abdullatif (Institute of Electrical and Electronics Engineers (IEEE), 2024)
The success of organizations today relies heavily on their intellectual capital, as knowledge is a key resource for value creation. Sharing and transferring knowledge enhances its value, embedding it within an organizations processes and boosting competitiveness. This study focuses on the Yemen public telecommunication corporation (YPTC), which has adopted a knowledge-focused management approach. This study aims to explore challenges related to knowledge transfer in Yemens public sector, where such research is lacking. Using a descriptive and analytical method, data were collected via a questionnaire from 200 employees, yielding a response rate of 88%. The findings indicate a high level of knowledge transfer at YPTC, with individual, organizational, and technological factors identified as significant influences. The key barriers include trust, information technology support, motivation, and social networks.